The Effectiveness of an Integrated Law Enforcement Center (GAKKUMDU) Policy on Handling 2019 Election Criminal Violations in North Sulawesi - Liando, Daud M. (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
In handling election criminal violations, the policies of the Election Law Enforcement Center or Gakumdu are regulated. Gakumdu consists of elements from Bawaslu, the prosecutor’s office and the police. The aim of the establishment of Gakumdu is to encourage the election trial to take place quickly and accurately. This must be done because the election process is bound by a strict schedule and stages, so it is impossible for the election stages to be adjusted to the ordinary judicial process. This study aims to analyze whether the Sentra Gakkumdu Policy in North Sulawesi has had an impact on the effectiveness of election law enforcement in Indonesia. What are the obstacles to the Gakkumdu Sentra Policy in the electoral law enforcement process in Indonesia and what solutions can be made so that the role of the Gakkumdu Sentra Policy is more effective in enforcing election law. The results of the analysis concluded that the handling of alleged violations of election crimes by the Sentra Gakkumdu in the 2019 election in Sulawesi was not effective because there were provisions both in the election law and other regulations that hindered the work of the Sentra Gakkumdu. There are often differences in legal perceptions among members of the Gakkumdu in determining whether a request fulfills the element of a violation or not. Not all districts/cities have a Prosecutor’s Office or a Police Office.